Playful absence / absence of play:: rethinking the design studio in online environments - Lehtonen, Miikka; Khamisani, Noorin; Gatto, Gionata (Design and Technology Education: An International Journal, 2021)
While the pandemic has had a tremendous negative impact on societies, it has nonetheless provided us with a sort of living lab for investigating and exposing consolidated models of design education. The design studio, often conceptualized as a spatio-temporally inhabited milieu with translocal norms and conventions, became a blended environment where students and instructors alike had to establish new conventions and ways of knowing and inquiring. Employing Sicart’s notions of play and playfulness as our theoretical lens, this paper argues how online learning has opened up a space for students and instructors to blur the boundaries of the design studio through the intersection of play and absence. Absence of things gives rise to being playful, and absence of play is required to sustain collaborative play. Through student interviews and our personal reflections, our findings reveal how play spatio-temporally fragments the design studio. In the absence of pre-existing conventions, play negotiates the boundaries of the design studio. Moreover, creating the virtual design studio can be understood as an emergent act of play; by being playful, we partly leave behind the norms and assumptions of the physical design studio to create something new. In addition, and paradoxically, creating a personalized and community-based way of being helped in seeing the immediate surroundings as the studio. Here, creating new methods for working in the studio playfully created boundaries for play. Theoretical and pedagogical implications shed light on the future of design studio and education as spaces that can be collaboratively enacted.